Genome-Wide Association Mapping for Yield and Related Traits Under Drought Stressed and Non-stressed Environments in Wheat - Rabbi, S. M. Hisam A.; Kumar, Ajay; Mohajeri Naraghi, Sepehr; Simsek, Senay; Sapkota, Suraj; Solanki, Shyam; Alamri, Mohammed S.; Elias, Elias M.; Kianian, Shahryar; Missaoui, Ali; Mergoum, Mohamed (Frontiers in Genetics, 2021)
Understanding the genetics of drought tolerance in hard red spring wheat (HRSW) in the northern USA is a prerequisite for developing drought-tolerant cultivars for this region. An association mapping (AM) study for drought tolerance in spring wheat in the northern USA was undertaken using 361 wheat genotypes and Infinium 90K Single Nucleotide polymorphism (SNP) assay. The genotypes were evaluated in different 9 locations of North Dakota (ND) for plant height (PH), days to heading (DH), yield (YLD), test weight (TW), and thousand kernel weight (TKW) under rain-fed conditions. Rainfall data and soil type of the locations were used to assess drought conditions. Illumina’s Infinium 90K SNP assay was used for genotyping and a mixed linear model (MLM) with (PC+K) was used for marker trait association. A total of 69 consistent QTL involved with drought tolerance related traits were identified, with p ≤ 0.001. The chromosomes 1A, 3A, 3B, 4B, 4D, 5B, 6A, and 6B were identified to harbor major QTL for drought tolerance. Six potential novel QTL were identified on chromosomes 3D, 4A, 5B, 7A, and 7B. The novel QTL were identified for DH, PH and TKW. The findings of this study can be used in marker-assisted selection (MAS) for drought-tolerance breeding in spring wheat.